A phase-field model for mixed-mode elastoplastic fatigue crack. (14th April 2023) - Xie, Qikun; Qi, Hongyu; Li, Shaolin; Yang, Xiaoguang; Shi, Duoqi
Highlights: A new phase field model for mixed-mode elasto-plastic fatigue crack is proposed. The effect of fatigue parameters of this model is analyzed. The calculated results under different mode I/II critical energy release rate ratios for elasto-plastic fatigue crack are compared. The proposed approach is applied successfully to the mixed-mode fatigue crack on several kinds of specimens. Abstract: One of the most common damage modes of aero-engine hot-end components is crack. Because of the complicated geometry and harsh working environment, the crack is typically in a mixed-mode and under elastoplastic conditions. The phase-field fracture method is a numerical simulation method that has recently attracted extensive attention. However, attention toward material damage and crack initiation before the crack emerges is lacking to solve the problem of elastoplastic mixed-mode fatigue crack propagation. In this study, an enhanced phase-field fracture method addresses this issue and predicts the propagation behavior of the elastoplastic mixed-mode fatigue crack. The effect of some parameters of this model is analyzed. This achievement is a significant contribution to the safety of aircraft engines and a novel method that can be further improved to solve problems in the future.